Alteration in Soil Carbohydrates Consequent Upon Growing Eucalyptus in Natural Sal (Shorea robusta) Areas or Doon Valley - Singhal, R. M.; Dev, Satinder (Indian Forester, 1977)
Total polysaccharide content of soil hydrolysates (hexose, methyl hexoses and 6-deoxy hexoses) which reacts with anthrone was measured in some sal forest soils of Doon Valley, growing presently Eucalyptus. The comparative study of the nature and content or carbohydrates in the soils under two vegetations reveals that the growing of Eucalyptus in sal areas has not only increased the content but also altered their nature in the following quinquennium, by way of increased polymerisation and resistance towards electrolytes, and decreased dispersion, which are helpful from the point of view of structure formation and fertility status.